Batch and sampling time exert a larger influence on the fungal community than gastrointestinal location in model animals: A meaningful case study - Li, Jiayan; Chen, Daiwen; Yu, Bing; He, Jun; Huang, Zhiqing; Zheng, Ping; Mao, Xiangbing; Li, Hua; Yu, Jie; Luo, Junqiu; Yan, Hui; Luo, Yuheng (Frontiers in Nutrition, 2022)
Fungi play a fundamental role in intestinal ecosystem and health, but our knowledge of fungal composition and distribution in the whole gastrointestinal tract (GIT) is very limited. The physiological similarity between humans and pigs in terms of digestive and associated metabolic processes places the pig in a superior position over other non-primate models. Here, we aimed to characterize the diversity and composition of fungi in the GIT of pigs. Using high-throughput sequencing, we evaluated the fungal community in different locations of GIT of 11 pigs with 128.41±1.25 kg body weight acquired successively. Among them, five pigs were sacrificed in April 2019 (batch 1) and the other six were sacrificed in January 2020 (batch 2). All subjects with similar genetic backgrounds, housing, management and diet. Finally, no significant difference was found in the α-diversity (Richness) of fungal community among all intestinal segments. Basidiomycota and Ascomycota were the two predominant fungal phyla, but batch 1 harbored a notably high abundance of Basidiomycota, and batch 2 harbored a high abundance of Ascomycota. Moreover, the two batches harbored completely different fungal compositions and core fungal genera. FUNGuild (Fungal Functional Guild) analysis revealed that most of the fungal species present in the GIT were saprotroph, plant pathogen and animal endosymbiont. Our study is the first to report that even under the same condition, large variations in fungal composition in the host GIT still occur from batch-to-batch and sampling time. The implications of our observations serve as references to the development of better models of the human gut.